MYB24 orchestrates terpene and flavonol metabolism as light responses to anthocyanin depletion in variegated grape berries - Zhang, Chen; Dai, Zhanwu; Ferrier, Thilia; Orduña, Luis; Santiago, Antonio; Peris, Arnau; Wong, Darren C J; Kappel, Christian; Savoi, Stefania; Loyola, Rodrigo; Amato, Alessandra; Kozak, Bartosz; et al. (The Plant cell, 2023)
Abstract Variegation is a rare type of mosaicism not fully studied in plants, especially fruits. We examined red and white sections of grape (Vitis vinifera cv. ‘Béquignol’) variegated berries and found that accumulation of products from branches of the phenylpropanoid and isoprenoid pathways showed an opposite tendency. Light-responsive flavonol and monoterpene levels increased in anthocyanin-depleted areas in correlation with increasing MYB24 expression. Cistrome analysis suggested that MYB24 binds to the promoters of 22 terpene synthase (TPS) genes, as well as 32 photosynthesis/light-related genes, including carotenoid pathway members, the flavonol regulator HY5 HOMOLOGUE (HYH), and other radiation response genes. Indeed, TPS35, TPS09, the carotenoid isomerase gene CRTISO2, and HYH were activated in the presence of MYB24 and MYC2. We suggest that MYB24 modulates ultraviolet and high-intensity visible light stress responses that include terpene and flavonol synthesis and potentially affects carotenoids. The MYB24 regulatory network is developmentally triggered after the onset of berry ripening, while the absence of anthocyanin sunscreens accelerates its activation, likely in a dose-dependent manner due to increased radiation exposure. Anthocyanins and flavonols in variegated berry skins act as effective sunscreens but for different wavelength ranges. The expression patterns of stress marker genes in red and white sections of ‘Béquignol’ berries strongly suggest that MYB24 promotes light stress amelioration but only partly succeeds during late ripening. MYB24 controls metabolic responses in skin sections of variegated grape berries lacking anthocyanin to cope with high-intensity and UV light stress, promoting terpene and flavonol accumulation.